2020
DOI: 10.46572/nat.2020.8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the experience and mood of COVID-19 pandemic care nurses

Abstract: Epidemics and pandemics have affected many societies at various times throughout human history. In the 21st century, the world is still struggling with epidemics and pandemics. Nurses play important roles in healthcare practices during infectious disease pandemics and other epidemic diseases. Therefore, they are at risk of direct patient care and exposure to contagious diseases. In this study, during the COVID-19 outbreak, pandemic care nurses; It is aimed to examine their experiences and moods with a question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…Most importantly, it has been suggested that isolation can further increase employees' psychological stress by causing to decrease in psychosocial support provided by the family (28). In the current study, no significant difference was found between the need to take professional psychological support during the pandemic and the frequency of isolating themselves from their families.…”
Section: Resultscontrasting
confidence: 69%
“…Most importantly, it has been suggested that isolation can further increase employees' psychological stress by causing to decrease in psychosocial support provided by the family (28). In the current study, no significant difference was found between the need to take professional psychological support during the pandemic and the frequency of isolating themselves from their families.…”
Section: Resultscontrasting
confidence: 69%
“…Previous research has reported that the number of children nurses have did not correlate with their psychological state during the pandemic. 4 It is an unsurprising result that having children increases fear of transmission. However, additional research is warranted to evaluate the reason for lower levels of coronaphobia in nurses with three or more children.…”
Section: Discussionmentioning
confidence: 99%
“…They provide direct care to patients and maintain close physical contact, leading to direct exposure to infectious pathogens and a high risk of contracting the virus. 4 Pandemics endanger both the physical and psychosocial health of health care professionals who are directly involved in the diagnosis, treatment, and care of infected patients. The COVID-19 pandemic has been no less serious in this regard.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses provide hands-on care and treatment for both COVID-19 patients and other patients. They are more likely to contract the virus because they are exposed to it as they care for those in need (16). According to the International Council of Nurses (October 20, 2020), more than 1,500 nurses in 44 countries and more than 20,000 healthcare workers worldwide died from COVID-19 (17).…”
mentioning
confidence: 99%